2008
DOI: 10.7589/0090-3558-44.3.701
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Bovine Tuberculosis in a Wild Red Fox (Vulpes vulpes) in Southern Spain

Abstract: A wild-caught, adult red fox (Vulpes vulpes) from Doñana National Park (southern Spain), in very poor condition, died during anesthesia. At necropsy, the submandibular, retropharyngeal, mediastinal, axillary, mesenteric, and popliteal lymph nodes were enlarged, and the right submandibular and mesenteric lymph nodes had hard, white-colored concretions (calcifications). Multiple white pinpoint foci were observed in the lungs, and abscesses were present in the left dorsal lung lobes. No lesions were seen in tonsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 20 publications
2
37
0
Order By: Relevance
“…Since canids only rarely develop lesions when they have a generalized M. bovis infection (Millan et al 2008), the lack of paratuberculosis and bTB-compatible lesions was not a surprising finding in this study. However, this lack of visible lesions in a large sample of wild canids, along with the absence of microscopic lesions in the studied subsample, adds to the view that wild canids play no relevant role in the epidemiology of mycobacterial diseases in Southwestern Europe.…”
Section: Discussionmentioning
confidence: 55%
“…Since canids only rarely develop lesions when they have a generalized M. bovis infection (Millan et al 2008), the lack of paratuberculosis and bTB-compatible lesions was not a surprising finding in this study. However, this lack of visible lesions in a large sample of wild canids, along with the absence of microscopic lesions in the studied subsample, adds to the view that wild canids play no relevant role in the epidemiology of mycobacterial diseases in Southwestern Europe.…”
Section: Discussionmentioning
confidence: 55%
“…The results suggest that M. bovis circulates widely in the studied area, which is a serious concern for wildlife. Our findings have also revealed a public health concern because veterinarians and other professional workers, as well as hunters who come into contact with these species, have a high risk of being infected when handling infected samples and tissues (Millán et al 2008).…”
Section: Resultsmentioning
confidence: 69%
“…The extent to which infected red foxes may be involved in the epidemiology of M. bovis in other wild mammals remains unknown. Foxes most probably become infected after scavenging of infected wild ungulate carcasses (Millán et al 2008), because bovine tuberculosis was previously reported in wild ungulates in the studied area (Santos, et al 2009). …”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations